HUBUNGAN TINGKAT STRESS MAHASISWA DENGAN POLA HIDUP TIDAK SEHAT - Tsamra, Dasilta Ing; Zahra, Siti Nazhifatu (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
Stress is a condition where a person experiences excessive levels of tension or pressure physically or emotionally. This condition can be caused by various factors. The purpose of this study was to determine and analyze the relationship between stress levels and unhealthy lifestyles. This research design uses a correlation method with purposive sampling technique. The population in this study were students of the Faculty of Islamic Religion, Ibn Khaldun University, Bogor. The sample taken was 50 people and analyzed using Pearson's product moment correlation. The results showed that there is a perfect but strong negative relationship between the level of stress experienced by students and unhealthy lifestyles.